Limited efficacy of adjunctive therapy in a case of severe herpes simplex virus encephalitis: A case report and literature review - Xiao-Ling Zhong; Chen-Li Yang; Xiao-Long Yu; Ling Wang (IDCases, 2025)
Herpes simplex virus-1 (HSV-1) encephalitis is a severe neurological disease with high mortality and morbidity despite antiviral therapy. The role of adjunctive immunomodulatory treatments like intravenous immunoglobulin (IVIG) and glucocorticoids remains uncertain. We report a fatal case of severe HSV-1 encephalitis in a 59-year-old man who developed hemorrhagic necrosis despite combined treatment with acyclovir, IVIG (0.4 g/kg/day), and methylprednisolone (80 mg/day). CSF PCR and MRI confirmed the diagnosis, with subsequent imaging showing progressive left hemispheric hemorrhage requiring surgical evacuation. The patient deteriorated neurologically and died on day 56. This case adds to growing evidence questioning the efficacy of adjunctive IVIG/steroids in advanced HSV-1 encephalitis, particularly with hemorrhagic complications. While some studies suggest potential benefits during the inflammatory phase, our experience highlights their limitations in critical cases. More research is needed to identify which patients might benefit from immunomodulation and optimal treatment timing.